2019
DOI: 10.1002/pros.23794
|View full text |Cite
|
Sign up to set email alerts
|

Long‐lasting bladder overactivity and bladder afferent hyperexcitability in rats with chemically‐induced prostatic inflammation

Abstract: Background: Benign prostatic hyperplasia (BPH) is one of the major causes of lower urinary tract symptoms (LUTS), including storage LUTS such as urinary frequency and urgency. Recently, a growing number of clinical studies indicate that prostatic inflammation could be an important pathophysiological mechanism inducing storage LUTS in patients with BPH. Here we aimed to investigate whether nonbacterial prostatic inflammation in a rat model induced by intraprostatic formalin injection can lead to longlasting bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The present study showed a significantly higher prostate-tobody weight index in aged rats, suggesting that age-related conditions may induce a partial urethral obstruction affecting urination due to complicated voiding patterns in MOR. This observation suggest that it is possible to avoid chemically induced changes in prostate size [16,17]. The immunofluorescence results also revealed an increased presence of neurofilaments in MOR, supporting the possibility that pathological conditions stimulate prostatic innervation and consequently the overgrowth of the gland [18].…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The present study showed a significantly higher prostate-tobody weight index in aged rats, suggesting that age-related conditions may induce a partial urethral obstruction affecting urination due to complicated voiding patterns in MOR. This observation suggest that it is possible to avoid chemically induced changes in prostate size [16,17]. The immunofluorescence results also revealed an increased presence of neurofilaments in MOR, supporting the possibility that pathological conditions stimulate prostatic innervation and consequently the overgrowth of the gland [18].…”
Section: Discussionsupporting
confidence: 58%
“…Our results support this hypothesis by showing the coexistence of prostate enlargement, increased prostate innervation, and bladder hyperactivity in MOR. Indeed, in a recent study using a formalin-induced prostatic inflammation model in rats, hyperexcitability of afferent neurons combined with bladder overactivity was observed [ 16 ], supporting the idea of more complex interactions among the prostate, the urinary bladder, and afferent innervation and the possibility that a localized reflex may control both organs.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the present study, rats with formalin‐induced prostatic inflammation exhibited bladder overactivity without inflammatory changes in the bladder, suggesting that there is a mechanism that causes bladder overactivity without direct formalin infiltration into the bladder wall after intraprostatic formalin injection. In this regard, our recent studies showed that localized prostatic inflammation can evoke bladder overactivity and bladder afferent hyperexcitability up to 8 weeks after one‐time intraprostatic formalin injection and that bladder overactivity following prostatic inflammation is induced by prostate‐to‐bladder cross‐talk through activation of the pelvic nerve that contains dichotomized afferents innervating both bladder and prostate 13,14 . Taken together, it is plausible that bladder overactivity after prostatic inflammation was caused by afferent sensitization, rather than the direct local effects of formalin on the bladder in this study.…”
Section: Discussionmentioning
confidence: 50%
“…There was no significant difference in MVP or RV among three groups (bottom left and right in Figure 1B bladder overactivity following prostatic inflammation is induced by prostate-to-bladder cross-talk through activation of the pelvic nerve that contains dichotomized afferents innervating both bladder and prostate. 13,14 Taken together, it is plausible that bladder overactivity after prostatic inflammation was caused by afferent sensitization, rather than the direct local effects of formalin on the bladder in this study.…”
Section: Discussionmentioning
confidence: 75%